Therapy for Primary Vulvar Carcinoma - Herr, D.; Juhasz-Boess, I.; Solomayer, E. F. (Geburtshilfe und Frauenheilkunde, 2014)
The rather rare vulvar cancer is almost always a squamous cell carcinoma that mostly develops from an underlying VIN or HPV infection. In addition, lichen sclerosus et atrophicans, immune deficiency, nicotine abuse or anogenital intraepithelial neoplasias may play a role in the pathogenesis. Surgical therapy aims at an R0 resection in the sense of a complete vulvectomy or a radical local excision with, if necessary, plastic reconstruction. Also, the vulvar field resection with consideration of the compartment model has been discussed. Besides the classic inguinofemoral lymphadenectomy, in selected cases of vulvar cancer sentinel biopsies are performed by experienced surgeons in the larger centres. In contrast, systemic therapy plays only a subordinate role; in isolated cases down-staging by means of neoadjuvant chemotherapy may be useful. However, there is at present no indication for adjuvant chemotherapy. Neoadjuvant radiochemotherapy is also not to be recommended on account of its unfavourable ratio of efficacy to side effects. On the other hand adjuvant radiotherapy is indicated in cases of positive inguinal lymph nodes. According to the current data the indication should be made generously in such cases.
Keywords: vulva; cancer; therapy